Does landscape diversity and organic cultivation practices support biodiversity that render crucial ecosystem services? - Krishnan, Abhiram; Baby, Ashly; Viswan, Gopika; Hariraveendra, M.; Jose, Thomas; Sinu, Palatty Allesh; Krishnan, Smitha (2024)
Landscape diversity and organic cultivation practices support biodiversity and in particular the functional guilds that render crucial ecosystem services such as pollinators, soil microbiome, and invertebrate biocontrol agents. In this study we aim to use landscape matrices of diﬀerent land use types and agricultural practices to evaluate the responses of pollinators, invertebrate biocontrol agents and soil microbiomes that are extremely important for crop yield and quality in additional to other ecosystem services that they provide to adjoining landscapes.